An Analysis of Factors that Influenced Students English Speaking Ability of Elementary School Teacher Education Students at STKIP Al Islam Tunas Bangsa - Pamungkas, arimbi; Soraya, Rahayu (Jurnal Evaluasi dan Pembelajaran, 2024)
Speaking ability is one of the most important skills in English. Besides, the ability to speak English is also a challenging skill. This is due to various factors that influence it. This research aims to determine the factors that influence the ability to speak English. This research used a qualitative descriptive method. The subjects in this research were students of elementary school teacher education program STKIP Al Islam Tunas Bangsa in the first semester. Data was obtained through observation and interviews. The results of the research showed that the ability to speak English is influenced by several factors such as lack of vocabulary, lack of self-confidence, low motivation, mother tongue, and difficulties in pronunciation.